Hubungan Kadar Debu Terhirup (Respirable) Dengan Kapasitas Vital Paksa Paru Pada Pekerja Mebel Kayu di Kota Jayapura - Irjayanti, Apriyana; Nurjazuli, Nurjazuli; Suwondo, Ari (Jurnal Kesehatan Lingkungan Indonesia, 2012)
Background: Furniture workers is one of the informal workers. Workers in this group are have not receivedoccupational health services as expected. Pulmonary function disorders due to work which the most commonespecially in the wood processing industry.Methods: Research purpose was to analyze the relationship among factors of respirable dust level, age, working years, nutrition status, smoking habit, exercise habit, duration of exposure, and use of the PPE with the lung forced vital capacity on wood furniture workers in Jayapura. This study was an observational research with cross sectional approach and a sample of 40 man taken by purposive sampling. Respirable dust levels were measured using the Personal Sample Pump, tested for dust analysis using the Gravimetric method, while in the lung forced vital capacity was measured with Spirometry, and other data obtained by interviews. Data analysis using the Kendallâ€™s Tau and Mann Whitney tests (Â± = 0,05).Results: The results showed levels of respirable dust in excess of TLV (> 1 mg/m3) for 3 respondents (7,5 %), thehighest dust levels are 1.220 mg/m3 and the lowest at 0,020 mg/m3, the average value of 0,222 and SD 0,282 while for lung forced vital capacity by 23 respondents (42,5 %) had disorders lung function (restriction), 5 respondents (12,5%) had moderate restriction of 18 respondents (45%) had mild restriction with the highest value is 183 % FVC and lowest at 51 %, the average value of 84,40 % and SD 25,289. Statistical tests showed association (p = 0,05) between the levels of respirable dust (p-value = 0,050) with lung forced vital capacity, and that show no association (p > 0,05) is age (p-value = 0,916), working years (p-value = 0,991), BMI (p-value < 0,084), smoking habit (p-value = 0,158), exercise habit (p-value = 0,663), duration of exposure (p-value = 0,718), and use of the PPE (p-value = 0,658).Conclusion: The factors that affect the lung forced vital capacity in wood furniture workers in Jayapura is respirabledust levels.Keywords : Respirable Dust Levels, Lung Forced Vital Capacity, Wood Furniture Workers